Theoretical analysis of sensitivity enhancement of surface plasmon resonance biosensor with zinc oxide and blue phosphorus/MoS2 heterostructure - Singh, Sachin; Sharma, Anuj K.; Lohia, Pooja; Dwivedi, D.K. (Optik (Stuttgart), 2021)
In this paper, an ultrasensitive surface plasmon resonance (SPR) biosensor structure (CaF2 Prism /ZnO/Au/BlueP-MoS2/Sensing medium) based on angular interrogation technique has been studied to see the effect of Blue Phosphorus/MoS2 heterostructure with an adhesive layer of zinc oxide (ZnO). The adhesive layer is ZnO used between calcium fluoride (CaF2) prism and gold (Au) layer. Transfer matrix method is used for numerical analysis at operating wavelength 633 nm. The layers ZnO and Blue Phosphorus/MoS2 heterostructure are optimized to achieve the maximum sensitivity with minimum reflectance. The performance parameters, such as sensitivity (2280RIU−1), quality factor (56.211RIU−1), detection accuracy (0.2810), full width at half maximum (4.0561), and limit of detection (4.3859 × 10−6) are calculated for proposed SPR biosensor at room temperature. For two layers of BlueP/MoS2 heterostructure, the maximum sensitivity is 2350RIU−1. The result shows that the sensitivity of proposed structure is 17.5% greater as compared to the conventional structure. Transverse magnetic (TM) field is plotted, and the value of penetration depth is calculated as 145.25 nm for proposed SPR sensor. The proposed SPR sensor could be very useful in the SPR chip to detect biomolecules or analyte in visible range.